Efficacy of fumigation Medang wood (Chinnamomum javanicum) at different times against Schizophyllum commune Fries fungus - Farah Diba; Lolyta Sisillia; Juan Arif Tertiadi (Jurnal Biologi Tropis, 2021)
The use of wood for the timber industry increases, but wood with a high natural durability class, especially class I & II was limited. Efforts to improve the quality of wood are needed. The research purposed to increase the durability of Medang wood (Chinnamomum javanicum) with the preservation methods using fumigation and evaluated againstÃÂ Schizophyllum communeÃÂ Fries fungi. Medang wood from gubal area was achieved from Kubu Raya Regency and made into a sample for preservation treatment measuring 5 cm x 2 cm x 2 cm. The wood preservation methods used fumigation. The fumigation process used an oven and time of fumigation consisting of 12 hours, 24 hours, and 36 hours. The temperature process was 80oC. After preservation, the wood was tested against Schizophyllum communeÃÂ Fries based on SNI 7207-2014. The result of preservation showed that the fumigation process changed the color of Medang wood. The color changed from white pale into brown (12 hours fumigation), dark brown (24 hours fumigation), and very dark brown (36 hours fumigation). The weight loss of Medang wood after 12 weeks attacked byÃÂ Schizophyllum communeÃÂ Fries fungi was range between 2.45% - 3.44%. The weight loss of Medang wood on treatment 12 hours fumigation was 3.44%, on treatment 24 hours was 3.34% and on the treatment of 36 hours was 2.45%. After the fumigation methods, the durability of Medang wood increased into II class. The compound from smoke during the fumigation process, which functions as antifungi, was phenol. The optimum treatment to increase the durability of Medang wood was fumigation for 36 hours with a temperature of 80oC.